EFEKTIVITAS PROGRAM âMENGASUH DENGAN BIJAKâ UNTUK MENINGKATKAN KUALITAS PENGASUHAN ORANGTUA (IBU) YANG MEMILIKI ANAK AGRESIF - , DEWI MUFIDATUL UMMAH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The emergence of emotional and behavioral disorders like aggressive child needed an effort of more intensive care from the parents. Positive parenting was an important factor in improving the development of child. The purpose of this research was to find out the effectiveness of program âMengasuh dengan Bijakâ that was inspired with triple p and the adaptation of BFI (Behavioral Family Intervention). The participant in this study contained of parent (mother) who has aggressive child in 2 Elementary School in Yogyakarta (N=14). The participant was divided into two, group experiment with program âMengasuh dengan Bijakâ (7 persons) and group control (7 persons). The quasi experiment method untreated pretest and posttest was designed to this study. Data analysis used was non parametric and qualitative analysis. This study was expected to improve care skill of parents in order that it can give affect at the aggressive behavior of child. The result of this study showed that program âMengasuh dengan Bijakâ can improve parenting quality of parents who has aggressive children.